Rheological Properties and Structural Characterization of Konjac Glucomannan/Arabic Gum Composite Hydrosol - Xiaoying JI; Yang HUANG; Xi HU; Wei ZHANG; Di ZHANG; Jiawei ZHANG; Dongliang LI (Shipin gongye ke-ji, 2022)
In order to study the properties of konjac glucomannan (KGM)/gum arabic (GA) composite hydrosol and improve its application performance in food industry, the rheological properties and microstructure of KGM/GA composite hydrosol with different proportions were studied by rheometer, FT-IR, XRD and SEM. The rheological properties and structural characterization of KGM/GA composite hydrosol with different mixing ratio were discussed. The results showed that KGM and GA had a good compatibility, and they could play a synergistic role in a certain mixing ratio. GA could improve the rheology and transparency of KGM, and KGM could improve the viscoelasticity and stability of GA. KGM and GA could promote mutual cross-linking through the increase of hydrogen bonds and the decrease of acetyl groups, strengthen the intermolecular force of the composite hydrosol system and form a uniform and regular structure. When KGM:GA was 5:5(w/w), the KGM/GA composite hydrosol with most excellent comprehensive properties was obtained. Compared with KGM single system, the transparency of the sample increased by 65.82% and the crystallinity was enhanced by 14.57%. And the sample had moderate viscosity, high stability and good viscoelasticity, it was expected to provide some theoretical reference for the development of food adhesives and dietary fiber drinks.